BIOSENSOR UNTUK ANALISIS UREA BERDASARKAN PADA APLIKASI ENZIM UREASE DAN ELEKTRODA TUNGSTEN - Bambang Widihastono (Research Center for Chemistry - LIPI, 1993)
This study describes the development of a potentiometric biosensor for the determination of urea. The sensor was constructed by combining a tungsten wire with an enzyme, urease, physically immobilized in polyvinylchloride (PVC). The fabrication of the sensor was carried out by coating a tungsten wire with the immobilized urease. The changes in pH resulted from the enzyme-catalyzed hydrolysis of urea is measured with the tungsten electrode and shown to be proportional to the log of concentration of urea in sample solutions over a limited concentration range. Urea Sensor prepared in this study gives an almost linear response with the log of concentration in the range of 0.1 - 10.0 mM, and the calibration slope wasfound to be 52 mV Vper decade change in urea concentration.